المأساة الوطنية في الرواية الجزائرية : قراءة في نماذج من الرواية الجزائرية الجديدة - هيمة, عبد الحميد (Sciences humaines, 2014)
عرفت الرواية الجزائرية –  نتيجة لظاهرة الإرهاب - تحولات هامة على مستوى المضمون، والبناء الفني، فنقلت لنا مظاهر العنف والإرهاب الأعمى الذي حصد أرواح آلاف الجزائريين، كما عبرت عن المأساة الوطنية بصورة فجائعية، وبأدوات فنية متفاوتة من حيث النضج والتطور الفني.          وفي هذا البحث سنحاول الكشف عن تجليات المأساة الوطنية في الخطاب الروائي الجزائري المعاصر من خلال  روايتين وهما رواية " الشمعة والدهاليز،  للطاهر وطار"، و رواية " وسيدة المقام " لواسيني الأعرج . The Algerian novel has known considerable changes both at the level of content and artistic structure due to the phenomenon of terrorism. It has brought aspects of  violence and blind terrorism that led to the loss of thousands of lives among Algerians. It has, morever, expressed grievously and using different aritistic tools the national tragedy. The present study is an attempt to inquire into the national tragedy in the Algerian modern novelist discourse through three novels : ‘The Candle and the Corridors’ by Tahar Wattar,’ The Lady of the Situation’ by Wassini Laradj.